Analisis ekspor kayu manis Indonesia ke Amerika Serikat - Yulmi Nur Asrini; Siti Hodijah; Nurhayani Nurhayani (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study analyzes Indonesian cinnamon export volume to the United States, export cinnamon prices, exchange rates, and domestic cinnamon production. In addition, to investigate the effect of export cinnamon prices, exchange rates, and domestic cinnamon production on Indonesian cinnamon exports to the United States in 2000-2017. The data used was obtained from the official website of the Indonesian Central Statistics Agency, United Nations Commodity Trade (COMTRADE), and the Plantation Service. The data analysis method used in this research is descriptive and quantitative analysis method with multiple linear regression analysis. Based on the multiple linear regression analysis results, it can be concluded that simultaneously export cinnamon prices, exchange rates, and domestic cinnamon production have a significant effect on Indonesian cinnamon exports to the United States. The exchange rate and domestic cinnamon production have a considerable impact, but the price of export cinnamon had no significant effect on Indonesia's cinnamon exports to the United States. Keywords: Export cinnamon, Price, Exchange rate, Production.